A solution for squeezing deformation control in tunnels using foamed concrete: A review. (10th October 2020) - Wu, Kui; Shao, Zhushan; Qin, Su
Highlights: Application of foamed concrete in tunnel support is implemented in two ways. Performance requirements for foamed concrete in squeezing tunnels are summarized. Basic constituents and typical properties of foamed concrete are reviewed. Design parameters and performance of foamed concrete elements are discussed. Abstract: Foamed concrete possesses characteristics such as high deformability and low density. Using foamed concrete in tunnel support is able to absorb a certain amount of rock creep deformation and reduce lining pressure, providing a good solution to deal with large deformation problems in squeezing tunnels. The application of foamed concrete in tunnel support is structurally implemented in two ways. To provide a comprehensive insight into application of foamed concrete in squeezing tunnels, this paper explains the mechanism of squeezing deformation of tunnel, proposes the performance requirements for foamed concrete used in squeezing tunnels, and also summarizes the basic constituents and typical properties of foamed concrete. Furthermore, this paper reviews researches of the design and practical application of foamed concrete elements in tunnel support, covering such areas as the constitutive models of foamed concrete, the important design parameters of foamed concrete elements, and the performance of tunnels using foamed concrete elements.